THE APPLICATION OF CONCEPT SENTENCE MODEL WITH FLASHCARD MEDIA IN IMPROVING NARRATIVE WRITING SKILLS OF THE FOURTH GRADE STUDENTS OF SDN 4 KUTOSARI IN ACADEMIC YEAR 2014/2015 - Umah, Khoirulli (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Application of Concept Sentence Model with Flashcard Media in Improving Narrative Writing Skills of The Fourth Grade Students of SDN 4 Kutosari In Academic Year 2014/2015. The objectives of the research are: to improve narrative writing skills. This research is a collaborative Classroom Action Research (CAR) that was conducted in three cycles. Subject of the research are fifth grade students of SDN 4 Kutosari in academic year of 2014/2015, totalling 32 students. Validity of data uses triangulation technique in the form of triangulation of data sources and data collecting technique. The sources of data in this research were students, fourth grade teacher, researcher, dan peers. Techniques of collecting data are test and non test. The results show that the application of concept sentence model with flashcard media can improve narrative writing skills with KKM ? 70 in the first cycle was 69,36%, 77,49% in the second cycle and 88,34% in the third cycle. Keywords: concept sentence, flashcard, narrative writing skills